2021
DOI: 10.7150/ijbs.61439
|View full text |Cite
|
Sign up to set email alerts
|

The role of RNA m5C modification in cancer metastasis

Abstract: Epigenetic modification plays a crucial regulatory role in the biological processes of eukaryotic cells. The recent characterization of DNA and RNA methylation is still ongoing. Tumor metastasis has long been an unconquerable feature in the fight against cancer. As an inevitable component of the epigenetic regulatory network, 5-methylcytosine is associated with multifarious cellular processes and systemic diseases, including cell migration and cancer metastasis. Recently, gratifying progress has been achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 145 publications
(236 reference statements)
0
67
0
Order By: Relevance
“…N6-Methyladenosine (m6A), N1-methyladenosine (m1A), m5C, N7-methylguanosine (m7G), and 5-hydroxymethylcytosine (hm5C) are common types of RNA methylation modifications [ 5 ]. RNA m5C methylation indicates that the fifth C position of RNA cytosine is modified by methylation, which is a major posttranscriptional modification of RNA [ 6 ]. RNA m5C methylation plays an essential role in the regulation of RNA translation, stability, exiting the nucleus, and other biological processes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…N6-Methyladenosine (m6A), N1-methyladenosine (m1A), m5C, N7-methylguanosine (m7G), and 5-hydroxymethylcytosine (hm5C) are common types of RNA methylation modifications [ 5 ]. RNA m5C methylation indicates that the fifth C position of RNA cytosine is modified by methylation, which is a major posttranscriptional modification of RNA [ 6 ]. RNA m5C methylation plays an essential role in the regulation of RNA translation, stability, exiting the nucleus, and other biological processes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Localization of DNMT2 as a shuttling protein in the nucleus and cytosol during the cell cycle indicates that this methyltransferase actively modifies nucleic acids in both cellular compartments, which has been validated experimentally for a variety of RNA types besides the DNA [17,19]. Moreover, previous reports demonstrated that the NSUN family could target mRNA, rRNA, mitochondrial DNA, and non-coding RNAs, apart from tRNAs, to add a methyl group to the cytosine base [20]. Aly/REF Export Factor (ALYREF), a reader protein in the m5C pathway, takes a role in exporting mRNAs modified primarily by NSUN2 [21].…”
Section: Introductionmentioning
confidence: 81%
“…We included 23 m6A and 12 m5C regulatory factors based on the literature ( Bohnsack et al, 2019 ; He et al, 2019 ; Zhang et al, 2021 ) (m6A: KIAA1429, WTAP, RBM15, RBM15B, METTL16, METTL3, METTL14, ZC3H13, ALKBH5, FTO, FMRP translational regulator 1 [FMR1], heterogeneous nuclear ribonucleoprotein A2/B1 [HNRNPA2B1], HNRNPC, IGFBP1, IGFBP2, IGFBP3, leucine-rich pentatricopeptide repeat-containing [LRPPRC], RBMX, YTHDC1, YTHDC2, YTHDF1, YTHDF2, and YTHDF3; m5C: TET1, TET2, TET3, NSUN2, NSUN3, NSUN4, NSUN5, NSUN6, NOP2, ALYREF, tRNA aspartic acid methyltransferase 1 [TRDMT1], and YBX1). We compared the gene expressions of these regulatory factors between the tumor and normal tissue groups.…”
Section: Methodsmentioning
confidence: 99%